2020
DOI: 10.1111/jbi.13944
|View full text |Cite
|
Sign up to set email alerts
|

Towards an extended framework for the general dynamic theory of biogeography

Abstract: Aim The General Dynamic Model of island biogeography (GDM) explains patterns of species richness on volcanic hotspot archipelagos with respect to island age (T) and area (A), most commonly employing what we here call semi‐log ATT2 and LogATT2 models. These can be considered direct extensions of semi‐log and power law species‐area relationships (SARs), with a hump‐shaped function of T modelling drivers of biodiversity over and above area per se. We compare these and related models and investigate their conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…ISARs were fitted using the logarithmic transformation of the Arrhenius power model (Carey et al., 2020). We compared the ISARs of different taxa/chorotypes using adjusted‐R 2 values as a measure of their goodness of fit.…”
Section: Methodsmentioning
confidence: 99%
“…ISARs were fitted using the logarithmic transformation of the Arrhenius power model (Carey et al., 2020). We compared the ISARs of different taxa/chorotypes using adjusted‐R 2 values as a measure of their goodness of fit.…”
Section: Methodsmentioning
confidence: 99%
“…We reported an original investigation based on high-quality floristic data for the largest set of Aeolian Islands and islets presently available (32 insular units, with respect to the seven units investigated by Carey et al, 2020). In addition, thanks to a recently assembled data set on vascular plant species occurrence across all the eight islands (Pasta et al in prep) and 24 islets (Lo Cascio & Pasta, 2020), the range of plant species richness that we used in the analysis was significantly larger than that used by Carey et al (2020) for the seven larger Aeolian Islands (288-658 species) and permitted the separation between native species (1-572 species) and alien species (0-94 species).…”
Section: Island Species-area Relationship Of Native and Alien Plant S...mentioning
confidence: 99%
“…To our knowledge, the only paper using plant diversity data from the Aeolian Archipelago to explore its biogeographical patterns is a study on the general dynamic model (GDM) of island biogeography, aiming to test the role of island age and area as predictors of species richness (Carey et al, 2020). By analysing raw data regarding the total species richness of various biota (vascular plants, birds, bryophytes, arthropods, molluscs) from eight volcanic archipelagos (Azores, Galapagos, Hawaii, Marquesas, Society Islands, Cape Verde Islands, Canary Islands and Aeolian Archipelago), Carey et al (2020) concluded that both species–area relationships and species–time relationships ‘should always be considered as potentially more parsimonious options’, supporting the value of this type of investigation even in the context of volcanic archipelagos, for which a more advanced theoretical framework (GDM) is available (Borregaard et al, 2016; Whittaker et al, 2008). In addition, the role of time in affecting the environmental and biological processes that can control the community assembly in insular systems has been conceptualised (Flantua et al, 2020) and Aeolian Islands, with their different ages, offer an opportunity to disentangle the role of time, specifically expecting lower species richness in islands with ongoing volcanic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since habitats change over time (due to changes in abiotic and biotic factors), the richness and assemblage of species present on islands will likewise change. The general dynamic model (GDM) of oceanic island biogeography proposes that each island has an environmentally determined carrying capacity associated with age, resulting from changes over time in the island's area, TC and habitat diversity (Carey et al, 2020; Whittaker et al, 2008). Richness of native and endemic species should follow a hump‐shaped relationship over time with the greatest number of species found at intermediate stages when the island reaches its presumed maximum carrying capacity.…”
Section: Introductionmentioning
confidence: 99%